Th2 Biased Immunity With Altered B Cell Profiles in Circulation of Patients With Sporotrichosis Caused by Sporothrix globosa - Zu, Jianjiao; Yao, Lei; Song, Yang; Cui, Yan; Guan, Mengqi; Chen, Ruili; Zhen, Yu; Li, Shanshan (Frontiers in Immunology, 2020)
Sporotrichosis is a subcutaneous mycotic infection, and Sporothrixglobosa is one of the causative agents with a worldwide distribution, notably in Asia. However, the immune profile in human sporotrichosis caused by S. globosa still remains obscure. Here, we demonstrated enhanced Th2 response in circulation with significant increases in Th2 frequency, Th2/Tregs as well as IL-4 seretion in patients. Elevated IL-17A+Th17 percentage was accompanied with reduced IL-17A level in serum, which may imply a dysfunction of this CD4+T subset in S. globosa infection. In addition, Th2 percentage, the ratios of Th2/Tregs and Th17/Tregs were all raised in patients with fixed cutaneous form, while only Th2/Tregs displayed increment in lymphocutaneous form. Meanwhile, the percentage of double negative B cells was significantly increased and positively correlated with Th2 and Tregs in whole patients. Except naïve B cells, all memory B cells together with Th2 cells increased in patients with short duration (less than 6 months), which may suggest a collaboration of T cells with altered B cell profile in human sporotrichosis caused by S. globosa. In consistent with the changes of IFN-γ+Th1, IL-4+Th2 and IL-17A+Th17 in patients with short duration, the percentages of these effector T cells all expanded when cocultured with S. globosa yeast cells in vitro. These data shed light on the potential involvement of peripheral T and B cell immunity against this mycotic infection and indicated that different immune responses existed in different stages of sporotrichosis; meanwhile different immune profile may contribute to different clinical manifestations of this disease.